2002
DOI: 10.1152/ajpendo.00038.2002
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acid-induced hepatic insulin resistance: a potential role for protein kinase C-δ

Abstract: The mechanisms of the impairment in hepatic glucose metabolism induced by free fatty acids (FFAs) and the importance of FFA oxidation in these mechanisms remain unclear. FFA-induced peripheral insulin resistance has been linked to membrane translocation of novel protein kinase C (PKC) isoforms, but the role of PKC in hepatic insulin resistance has not been assessed. To investigate the biochemical pathways that are induced by FFA in the liver and their relation to glucose metabolism in vivo, we determined endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
134
1
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(150 citation statements)
references
References 59 publications
(71 reference statements)
12
134
1
3
Order By: Relevance
“…Notably, protein kinase C␦ is markedly induced. This was also seen in the progressive insulin resistance induced by free fatty acid in liver, which was associated with a increase in hepatic protein kinase C␦ (19). Similar observations have been reported in the vascular endothelium (1).…”
Section: Adipocytes Differentiated In High Glucose Fail To Down-regulsupporting
confidence: 78%
“…Notably, protein kinase C␦ is markedly induced. This was also seen in the progressive insulin resistance induced by free fatty acid in liver, which was associated with a increase in hepatic protein kinase C␦ (19). Similar observations have been reported in the vascular endothelium (1).…”
Section: Adipocytes Differentiated In High Glucose Fail To Down-regulsupporting
confidence: 78%
“…Thus, insulin alone might not be sufficient to induce the adverse effects of PKC-␦ on insulin action. These effects of PKC-␦ had been reported after pharmacological activation using phorbol ester (32), stimulation with leptin (47), or lipid infusion (35). Following this aspect, it must be noted that we observed an insulin-dependent phosphorylation of Ser 357 , but this effect was weak compared with the phosphorylation intensity after stimulation with phorbol ester.…”
supporting
confidence: 83%
“…Data of the novel PKC isoform ␦ mirrored this positive and negative modulation of insulin signaling; PKC-␦ is shown to be important for insulin-stimulated glucose uptake (36), and it participates in the insulin-dependent activation of Akt (38). On the other hand, we and others have shown that activation of PKC-␦ by lipids and leptin is involved in the impairment of insulin signaling (35,47) and in the induction of apoptosis of insulin-secreting cells (48). Serine phosphorylation of IRS-1 appears to be a major mechanism for the adverse effects of PKC-␦ on insulin action (32,41,47).…”
Section: Discussionmentioning
confidence: 66%
“…Diacylglycerol is known to act as a second messenger for many signal transduction pathways, including the novel protein kinase C (PKC) family. PKC δ [27] and PKC θ [28] have been implicated in diacylglycerol-induced insulin resistance. Accordingly, we measured levels of these proteins in the liver and skeletal muscle of Il6 −/− and control mice.…”
Section: Resultsmentioning
confidence: 99%